Pilates Exercise and Resisted Muscle Training To Hip And Knee Muscle Im pairment In Improving Pain And Quality Of Life In Patients With Tibio Femoral Osteoarthritis (Academia Journal of Medicine, 2025)
Aim: The aim of the study is to compare the effect of pilates exercise and resisted muscle  training of hip and knee joint muscles to improve pain and quality of life in tibio femoral  osteoarthritis. Method: 50 patients diagnosed with tibiofemoral osteoarthritis were included in the study.  The patients were randomly assigned into 2 groups. Group A received pilates exercise on  mat for hip and knee joint muscle for 4 weeks and Group B received resisted muscle training  using theratube for hip and knee joint muscle for 4 weeks. Pre and post intervention measures  for KOOS (Knee Osteoarthritis Outcome Score) scale were observed and documented. Result & Conclusion: The results indicate that both group A and group B shows improvement  in all components of KOOS. But when compared between both groups, group A shows more  significant improvement in pain and symptom than group B.
Keywords: Tibiofemoral Osteoarthritis; KOOS Knee osteoarthritis outcome score; Pilates exercise